Sistem Pendukung Keputusan Penerimaan Beasiswa pada SMP Negeri 2 Padang dengan Menggunakan Metode Technique For Order Of Preference By Similarity To Ideal Solution Menggunakan Pemograman PHP dAN MYSQL - Harkamsyah Andrianof (Universitas Putra Indonesia YPTK Padang, 2018)
Assisted Decision System is an intellectual from human resource and computer capabilities to correct decisions in helping or replacing it in general, therefore the system will give a precise and accurate decisions in organizing scholarship data for them who really worth. Technique For Order Of Preference By Similarity To Ideal Solution is a method that had a concepts which the best chosen alternative. Not only has shortest interval from positive ideal solution, but also has the longest interval from the negative one. Used criteria in this system is variable according to scholarship provided by Institusion